Estimation and Controlling of Excavation Wall Deformation Using Elasto-plastic Calculation with Nonlinear Ground Considerations - Agustian, Yanyan; Setiawan, Asep; Herdian Bayu AshSiddiq, Raden (International Journal of Psychosocial Rehabilitation, 2020)
In the excavation work, the calculation of lateral pressure is very important because it concerns the safety and smoothness of construction work. In fact, in the field, the calculation of the movement of the retaining wall is very complex. This is because the soil has mechanical properties that are not linear, so it requires calculation in other ways, which also takes into account the nonlinearity of the soil and the spring properties of the soil and the retaining wall itself. The case study of this paper outlines the calculation of the nature of the soil and the retaining wall in order to estimate and evaluate the movement of the retaining wall during excavation work. The results of calculations show there is a good correlation between the results of calculations and the results of monitoring the movement in the field. So that this method can be used for similar calculations in excavation works.